Applied and Integrative Endocrinology Case: A 31-Year-Old Woman With Shortness of Breath, Chest Pain, Nausea, and Dizziness - Rob Zachow (MedEdPORTAL, 2012)
Abstract This case describes a 31-year-old woman with ovarian hyperstimulation syndrome (OHSS). The pathogenesis of her OHSS results in the development of a constellation of cardiopulmonary and body fluid imbalances. This case can be used in any small and/or large group setting; the suggested discussion topics can be modified for use within physiology and pathophysiology curriculum throughout undergraduate medical school. When combined with the reproductive endocrine aspects of the case, this exercise provides a rich platform for the discussion of female reproductive endocrinology, as well as the normal and compensatory function of integrated physiologic systems. I have used this exercise in both the large and small group setting. On a scale of 1–5 (1 indicating strongly disagree, 5 indicating strongly agree) the students were asked to evaluate the following as part of the end-of-course evaluation (2011): The applied medical sciences case, “A 31-year-old woman with shortness of breath, chest pain, nausea, and dizziness” was an effective learning exercise. Responses: 4.5 (0.4) The applied medical sciences case, “A 31-year-old woman with shortness of breath, chest pain, nausea, and dizziness” was an effective use of curricular time. Responses 4.1 (0.6) Written comments linked to this part of the evaluation were overwhelmingly positive: I most recently (March, 2012) used this case in the large group setting as the foundation for a review of the Renal-Endocrine course at RWJMS; data from this session are pending.